Clinico-Bacteriological profile & Effect of Home remedies on Acute Abscess - Vishnu Kumar Patel; Patel Patel; APS Gaharwar; GP Shrivastava; Rachna Gupta; Narmada Prasad Patel (International Journal of Medical Research and Review, 2014)
Acute abscess are very common in tropical countries like India. We have conducted this study to evaluate clinical & etiological profile of abscess.Design: Prospective study.Methodology: All patients with soft tissue abscesses either admitted in Surgery Department or attended Surgical OPD during the study period. Cases of small superficial abscesses managed in Out Patient Department. Data regarding the age, sex, hemoglobin, location of the abscess and cause if any, was tabulated.Results: Total 1065 cases were included in this study, 63.57% were male and 36.43% were female. Most common age groups were between 6-20 years (22.25% male and 10.89% female, total 33.15%) and 21-40 years (20.66% male and 14.02% females, total 35.31%). 81.78% patients belonged to lower socio-economic status. Pain and swelling were the most common presenting symptoms (99.06% and 99.15% respectively). Lower limb was the commonest site with 33.34% followed by upper limbs (23.66%). There was high percentage (40.46%) of pre-hospitalization home based interventions that increased the complication rate. Staphylococcus aureus was most common culprit organism in 72% cases (80 out of 111 cultures done). Causes were not known in 79.53% cases, but 7.32% cases developed abscesses after intramuscular injections.Conclusion: Soft tissue abscesses are more prevalent in lower socio-economic group and rainy season. In most of the cases, the cause is unknown; trauma and intramuscular injection are the leading underlying known causes of these abscesses. Use of home remedies had increased the complication rate.